2009
DOI: 10.1021/ja902893u
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Differential Performance of Rh2(esp)2 as a Catalyst for C−H Amination

Abstract: The continued development of selective and efficient reaction technologies for C-H amination necessitates a deeper understanding of the factors that affect catalyst stability. 1 Our earliest mechanistic studies on carbamate and sulfamate ester oxidation indicated that dinuclear rhodium-tetracarboxylate catalysts were subject to rapid ligand exchange, a process believed to initiate catalyst decomposition. 2 These findings motivated the design and synthesis of Rh 2 (esp) 2 , a complex derived from two, chelating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
110
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(117 citation statements)
references
References 12 publications
7
110
0
Order By: Relevance
“…Structural assignments of the m/z 1,186.9057 signal as [5] + and the m/z 1,080.0535 signal as [1•3] + are supported by the close correspondence of predicted and experimental isotope profiles ( Fig. 4C and Fig.…”
Section: S1c) Although the Intensity Of [7+na]supporting
confidence: 56%
See 3 more Smart Citations
“…Structural assignments of the m/z 1,186.9057 signal as [5] + and the m/z 1,080.0535 signal as [1•3] + are supported by the close correspondence of predicted and experimental isotope profiles ( Fig. 4C and Fig.…”
Section: S1c) Although the Intensity Of [7+na]supporting
confidence: 56%
“…In our experience, the oxidation of substrate by Rh-nitrene 6 seems to correlate with competitive formation of a mixed-valent (Rh 2+ /Rh 3+ ) dimer 8 that visibly colors the reaction solution red. Previous studies show that this red species is generated when Rh 2 (esp) 2 1, sulfamate 2, and oxidant 3 are mixed in solution (e.g., 0.3 mM 1 in chlorobenzene) (4,5,11). In this report, we provide direct evidence for the formation of species 8.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…[1] Sequential reaction processes that involve metal nitrenes are rare despite their electrophilicity, [2] which enables reaction with carbonhydrogen bonds or olefins. [3][4][5][6] Our mechanistic study of rhodium(II)-catalyzed carbazole formation from biaryl azides which suggested that CÀN bond formation preceded CÀH bond cleavage through a 4p-electron-5-atom electrocyclization. [7] Consequently, we anticipated that substrates lacking functionalizable C À H bonds might participate in a migratorial process where a new C À C bond is formed in addition to the C À N bond.…”
mentioning
confidence: 90%